Acute exercise-associated skin surface temperature changes after resistance training with different exercise intensities - Weigert, M.; Nitzsche, N.; Kunert, F.; Lösch, C.; Baumgärtel, L.; Schulz, H. (International Journal of Kinesiology & Sports Science, 2018)
Background: Studies showed, that changes in muscular metabolic-associated heat production and blood circulation during and after muscular work affect skin temperature (T) but the results are inconsistent and the effect of exercise intensity is unclear. Objective: This study investigated the intensity-dependent reaction of T on resistance training. Methods: Ten male students participated. After acclimatization (15 min), the participants completed 3x10 repetitions of unilateral biceps curl with 30, 50 or 70% of their one-repetition-maximum (1RM) in a randomized order. Skin temperature of the loaded and unloaded biceps was measured at rest (Trest), immediately following set 1, 2 and 3 (TS1,TS2,TS3) and 30 minutes post exercise (T1 - T30) with an infrared camera. Results: Two-way ANOVA detected a significant effect of the measuring time point on T (Trest to T30) of the loaded arm for 30% (Eta²=0.85), 50% (Eta²=0.88) and 70% 1RM (Eta²=0.85) and of the unloaded arm only for 30% 1RM (Eta²=0.41) (p<0.05) but time effects were independent of the exercise intensity (p>0.05). The T values at the different measuring time points (Trest - T30) did not differ between the intensities at any time point. The loaded arm showed a mean maximum T rise to Trest of 1.8°C and on average, maximum T was reached approximately 5 minutes after the third set. Conclusion: This study indicate a rise of T, which could be independent of the exercise intensity. Infrared thermography seems to be applicable to identify the primary used functional muscles in resistance training but this method seems not suitable to differentiate between exercise intensity from 30 to 70% 1RM.